2018
DOI: 10.1016/j.joule.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Durable and Efficient Hollow Porous Oxide Spinel Microspheres for Oxygen Reduction

Abstract: The oxygen reduction reaction performance of the hollow porous oxide spinel microspheres was investigated. The ZnMnCoO 4 possessed a high onset potential of 1.00 V and an outstanding durability in the alkaline solution. The electronic transition of Co 3+ ions was found to weaken the Co 3+ -OH bond and facilitate the O 2À /OH À displacement. Thus, it may offer promising potential for use as an effective catalyst with high oxygen reduction activity and durability in fuel cells and metal-air batteries, among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(101 citation statements)
references
References 28 publications
2
99
0
Order By: Relevance
“…[13,14] Recently,i twas reported that Fe substitution just served as as upportive core element in spinel, which can contribute to the long-term durability. [15] In this work, we present af acile strategy to activate Co 3+ Oct .C o À Ob ond length changes caused by replacement of Co by Fe can also affect the covalencyofthe bond. Moreover,N-doped carbon nanotubes (NCNTs) can act as an ideal conductive substrate for metal oxides,o wing to its high electrical conductivity, large surface area, and intrinsic flexibility.…”
Section: Redox-inert Fe 3+ Ions In Octahedral Sites Of Co-fespinel Oxmentioning
confidence: 99%
“…[13,14] Recently,i twas reported that Fe substitution just served as as upportive core element in spinel, which can contribute to the long-term durability. [15] In this work, we present af acile strategy to activate Co 3+ Oct .C o À Ob ond length changes caused by replacement of Co by Fe can also affect the covalencyofthe bond. Moreover,N-doped carbon nanotubes (NCNTs) can act as an ideal conductive substrate for metal oxides,o wing to its high electrical conductivity, large surface area, and intrinsic flexibility.…”
Section: Redox-inert Fe 3+ Ions In Octahedral Sites Of Co-fespinel Oxmentioning
confidence: 99%
“…The2 D porous structure ensures fast mass transport while the defined active sites (Ni-N 4 )e ffectively catalyze the ORR. [29,30] Such Co-O x sites effectively promote the breaking of the M-OH À bond as well as the O 2 2À /OH À exchange reaction. [29] Fori nstance,p erovskites (e.g.L aCO 3 )a nd AB 2 O 4 spinel with Co-O x sites with single-electron occupation of the e g orbital of the Co atom show ORR performance comparable to that of platinum-based electrocatalysts.…”
mentioning
confidence: 99%
“…[17] Apart from M-N x sites, [28] the catalytic activity of M-O x sites with unique electronic structures is intrinsically high for electrocatalytic ORR. [29][30][31] Therefore,i ncorporating molecular Co-O x structures within the highly conductive 2D conjugated MOFs hints at the promise for achieving superior catalytic ORR activity for fuel cells and metal-air batteries. [29,30] Such Co-O x sites effectively promote the breaking of the M-OH À bond as well as the O 2 2À /OH À exchange reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations